Universities’ Role in Regional Development: A Case Study of University for Development Studies, Ghana - Abonyi, U.K. (Journal of Education and Practice, 2016)
This study, employing an interpretive research paradigm, sought to investigate into how University for Development Studies (UDS) is responding to its regional development mandate with a specific focus on how it is responding to human capital development, innovation capabilities, and social and environmental development in northern Ghana. A study of this nature was deemed relevant and appropriate since UDS was established in 1992 under the PNDC Law 279 with an explicit mandate to blend its academic work with that of the community in order to provide constructive interaction between the two for the total development of northern Ghana. Despite the deplorable state of development in Northern Ghana, the regional development mandate of UDS in such a challenging environment has not attracted much attention in the literature. Findings from the study suggest that while UDS has appreciably linked its teaching, research, and service roles to the development needs of northern Ghana, it has a stronger link with the human capital development and social, cultural, and environmental development compared to developing the innovation capabilities of northern Ghana. It is, therefore, recommended that if UDS is seen as a key player in the development of Northern Ghana through its policy mandate, then, government and regional authorities need to create an enabling environment and put in place appropriate policy support structures to stimulate an effective engagement of UDS with the industrial sector and local businesses.
Keywords: Universities; Regional Development; Human Capital Development; Innovation; Ghana